Computer-Mediated Communication: Application to Vocational English Education - Thi Quynh Nhu Ho (Journal of Technical Education Science, 2024)
Recent research on the use of computer-mediated communication (CMC) tends to focus on how CMC occurs and how to effectively apply Internet-based technologies into classrooms in general while little evidence has been found on the application of CMC tools to teach English language for workplace purposes. Therefore, this article aims to explore the use of CMC as an alternative platform for teaching English for vocational purposes. For this purpose, the current paper is based on library research combining synthesis and analysis of more than thirty empirical and non-empirical articles which were published in journals, conference proceedings, books, and conference presentations. The findings center around specifying: (i) the characteristics of vocational English education and the key theoretical frameworks and pedagogical models that underpin the use of CMC in teaching English for vocational purposes; (ii) the impacts of CMC mode on the students’ language learning outcomes and vocational skill development, and (iii) the needed preparation of educators for the successful use of CMC. The results offer insights into the growth of CMC use as an effective platform in vocational English education.